Buddhist Ritual Attributes and Symbols in Russian and Foreign Historiography - N. G. Alfonso (Научный диалог)
The article is devoted to the analysis of research related to the ritual attributes and symbols of Vajrayāna Buddhism. Urgency of the study is conditioned by the fact that ritual symbolism plays a great role in the life of society, especially where Vajrayāna Buddhism is spread - in the countries of Himalayan region, Tibetan Autonomous region of China, in Mongolia, in among Buryats, Kalmyks and Tuvinians. Classification of scientific research by time periods and directions of research is proposed. A review of the relevant literature published from the end of the XIX century to the present day is made. Special attention is paid to modern scientific works in Ethnography and Art. The author dwells on the analysis of historiography by separate groups of ritual attributes and symbols - altar decorations, the prayer wheel and the Phur-pa - Tibetan ritual dagger. It is proved that until now only certain aspects of ritual attributes - external form, function in ritual, symbolic load - were studied by scientists. It is shown that today there is no full - value complex research devoted to Buddhist ritual subjects. The question of the need to develop a special method of ethnological analysis of ritual attributes, which should include a linguistic analysis of the name of the object, its iconographic characteristics, ways of functioning and the historical context of its existence is raised by the author.